2020
DOI: 10.1001/jamanetworkopen.2019.19940
|View full text |Cite
|
Sign up to set email alerts
|

Association of Prenatal Maternal Psychological Distress With Fetal Brain Growth, Metabolism, and Cortical Maturation

Abstract: IMPORTANCE Prenatal maternal stress is increasingly associated with adverse outcomes in pregnant women and their offspring. However, the association between maternal stress and human fetal brain growth and metabolism is unknown. OBJECTIVE To identify the association between prenatal maternal psychological distress and fetal brain growth, cortical maturation, and biochemical development using advanced 3-dimensional volumetric magnetic resonance imaging (MRI) and proton magnetic resonance spectroscopy (1H-MRS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
127
1
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 155 publications
(155 citation statements)
references
References 94 publications
8
127
1
5
Order By: Relevance
“…Our GLM analyses regarding hippocampal volumes did not find any significant main effects of PPD or moderating effect by newborn sex. However, a recent study observed smaller fetal hippocampal volumes in both sexes after exposure to maternal anxiety between GW 24 to 40 ( Wu et al, 2020 ). Increased prenatal anxiety has also been connected to slower bilateral hippocampal growth during the first 6 months of life.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Our GLM analyses regarding hippocampal volumes did not find any significant main effects of PPD or moderating effect by newborn sex. However, a recent study observed smaller fetal hippocampal volumes in both sexes after exposure to maternal anxiety between GW 24 to 40 ( Wu et al, 2020 ). Increased prenatal anxiety has also been connected to slower bilateral hippocampal growth during the first 6 months of life.…”
Section: Discussionmentioning
confidence: 93%
“…Evidence of a connection between PPD and altered cortical morphology is convincing in newborn and child studies ( Buss et al, 2010 , Lebel et al, 2016 , Qiu et al, 2015b , Sandman et al, 2012 , Sandman et al, 2015 ). However, the relationships between PPD and brain regions closely related to emotional, cognitive and memory functions – such as the amygdala and hippocampus ( Qiu et al, 2017 , Qiu et al, 2015a , Wen et al, 2017 , Wu et al, 2020 ) – are less studied. Alterations in these structures may explain attentional deficits and other behavioural problems in offspring ( Van den Bergh et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that pregnancy women who bear significantly psychological burden are more likely to develop mental disorders and impaired social function in the future 14 , 15 . Further, the mental problems during pregnancy can also adversely affect the cognitive, emotional, and physical development of children 16 18 . Therefore, more attentions should be paid to the mental health of this special population.…”
Section: Introductionmentioning
confidence: 99%
“…Sex differences in global, regional and brain tissue growth rates have been reported in fetuses and neonates, with male fetuses showing larger volumes and faster growth rates than female fetuses ( Wu et al, 2020 ; Gilmore et al, 2007 ). However, to date, no study has examined sex differences in fetal brain 1 H-MRS. Our study shows significantly lower metabolite concentrations for tCr (p = 0.02), and trend-level (p < 0.10) for tCh, tNAA and Ins in female fetuses during the 2nd trimester.…”
Section: Discussionmentioning
confidence: 99%